2021
DOI: 10.1111/dom.14288
|View full text |Cite
|
Sign up to set email alerts
|

A 52‐week randomized controlled trial of ipragliflozin or sitagliptin in type 2 diabetes combined with metformin: The N‐ISM study

Abstract: Aim To compare the long‐term efficacy of sodium‐glucose co‐transporter‐2 inhibitors and dipeptidyl peptidase‐4 inhibitors as second‐line drugs after metformin for patients not at high risk of atherosclerotic cardiovascular disease (ASCVD). Materials and methods In a 52‐week randomized open‐label trial, we compared ipragliflozin and sitagliptin in Japanese patients diagnosed with type 2 diabetes, without prior ASCVD and treated with metformin. The primary endpoint was a glycated haemoglobin (HbA1c) reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…The participants in these trials were aged between 18 to 70 years old. Among all included studies, ten trials reported changes in BMI and weight [28,29,[35][36][37][38][39][40][41][42], two studies only reported BMI [43,44], and six studies only reported body weight [45][46][47][48][49][50].…”
Section: Resultsmentioning
confidence: 99%
“…The participants in these trials were aged between 18 to 70 years old. Among all included studies, ten trials reported changes in BMI and weight [28,29,[35][36][37][38][39][40][41][42], two studies only reported BMI [43,44], and six studies only reported body weight [45][46][47][48][49][50].…”
Section: Resultsmentioning
confidence: 99%
“…Drug therapy and dietary interventions are effective ways to treat diabetes. Metformin, sulfonylureas, insulin, and other drugs can significantly relieve T2DM with a hypoglycemic effect, but they cannot prevent islet cell failure (Kitazawa et al, 2021;Taylor et al, 2021). Research on the dietary intervention of diabetes has been increasing rapidly, with multiple natural and nutritional products thought to benefit the treatment of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in blood pressure, excessive bodyweight and lipid abnormalities are important for type 2 diabetes mellitus management to prevent and manage diabetes‐related complications, including CVD 5,6 . Two previous Japanese studies reported no significant differences in improvements in glycemic and coronary risk factors between SGLT2i and DPP4i treatments 25,26 . However, a recent Italian multicenter, retrospective, real‐world study reported that the proportion of patients achieving simultaneous reduction of HbA1c ≥0.5%, bodyweight ≥2 kg and SBP ≥2 mmHg was greater in patients newly starting dapagliflozin than those newly starting a DPP4i (17.6% vs 11.7%, relative risk 1.50, 95% CI 1.21, 1.86, P < 0.001) 15 .…”
Section: Discussionmentioning
confidence: 99%